Effects of Stem Cell Therapy on Keloid Treatment: A Literature Review - Eric Eric; Maria Olivia Angeline; Belinda Layrenshia; Kelvin Kelvin; Louis Rianto; Nadya Nainggolan; Cindy Willyana; Shamyra Radiance; Rizka Saffana Alinda Putri (Jurnal Penelitian Pendidikan IPA, 2024)
Fibroblasts that produce excess collagen and growth factors play a role in the pathogenesis of keloid formation. In general, keloids are treated with intralesional corticosteroids alone or with a combination of other modalities, but the recurrence rate is still relatively high, so alternative treatments such as stem cells are being investigated, one of which is Mesenchymal Stem Cells (MSC), which have proven to be useful in healing keloids. Therefore, this literature review aims to discuss the effects of stem cell therapy in the treatment of keloids. In this literature review, 36 journals were used that discussed stem cell therapy in the treatment of keloids taken from various journal sources, namely Google Scholar, Pubmed, Medline, Ebsco, Hindawi, and Cochrane which were published within the last 10 years. According to the source, MSC is divided into 2 types, namely Adipose Mesenchymal Stem Cells (AMSC) and Bone Marrow Mesenchymal Stem Cells (BMMSC). In several studies, AMSC is known to reduce the expression of TGF-β1, COL-1, and COL-2 proteins, and has been shown to inhibit the proliferation of fibroblasts in keloid patients. Whereas in the BMMSC study that was applied with Hydroxybutyl chitosan (HBC) and Arg-Gly-Asp (RGD) hydrogels for 7 days, it was shown to significantly reduce nodular collagen fibers (p<0.05). Keloids occur due to excessive production of collagen and are influenced by various factors such as age, gender, skin color, and genetics. Stem cell therapy, such as MSC, has been proven in various studies to be an alternative treatment for keloids